UPAYA MENDAPATKAN GENOTIP KEDELAI EFISIEN UNSUR HARA P PADA LAHAN RENDAH P - Ahadiyat Yugi R.; Agus Riyanto (Universitas Tadulako, 2011)
In Indonesia, low soil P availability is the major constraint in upland area. Therefore, it is needed to find soybean varieties with characters efficient in P and high yield. The objective of this study was to evaluate P uptake, P efficiency, yield, morphological and physiological characters for selection of P efficient varieties. A Randomized Completely Block design was used with three replications. Seven varieties i.e. local, Slamet, Leuser, L1 503, S1 131(2), SL3 113(6), S1 053 and P applications i.e. without P and 36 kg P2O5 ha-1 were tested. Some variables such as plant height, shoot weight, leaf number, branch number, filled and unfilled of pod number, grain weight, P content, P uptake and efficiency were analyzed. Data was analysis by F test and followed by DMRT. The results showed that there were different responses on P uptake among genotypes under low P condition. Slamet, S1 053, SL3 113 (6) and Leuser had characters of high potential of yield and efficient in P uptake under P stress. Some characters could be used for variety selection of P efficient with high yield i.e. shoot and grain weight, and P efficiency.